2018
DOI: 10.1021/acs.macromol.7b02534
|View full text |Cite
|
Sign up to set email alerts
|

Molecular-Level Study of Photoorientation in Hydrogen-Bonded Azopolymer Complexes

Abstract: To optimize azobenzene-containing materials for applications such as rewritable waveguides and holographic data storage, it is imperative to understand the effect of the azobenzene structure on the photoresponse of the material. Supramolecular materials, in which a complexed photoactive azobenzene controls the motion or other properties of a passive polymer, are uniquely convenient for studying the impact of specific chemical modifications. Here, we use polarization modulation infrared structural absorbance sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 80 publications
(223 reference statements)
7
27
0
Order By: Relevance
“…In addition, besides photoisomerization, 28,29 azobenzene-containing polymers (azopolymers) show other interesting photoresponsive properties such as photoinduced orientation ( Fig. 2b and c), [30][31][32][33][34][35][36][37][38][39][40][41][42][43] formation of surface relief gratings (SRGs) (Fig. 2d), [44][45][46][47][48] photoactuation ( Fig.…”
Section: Si Wumentioning
confidence: 99%
“…In addition, besides photoisomerization, 28,29 azobenzene-containing polymers (azopolymers) show other interesting photoresponsive properties such as photoinduced orientation ( Fig. 2b and c), [30][31][32][33][34][35][36][37][38][39][40][41][42][43] formation of surface relief gratings (SRGs) (Fig. 2d), [44][45][46][47][48] photoactuation ( Fig.…”
Section: Si Wumentioning
confidence: 99%
“…116 An infrared technique called polarization-modulation FTIR structural absorbance spectroscopy (PM-IRSAS), 127 which can decouple the orientational effects originating from different chemical groups of the material system, was used to follow the molecular-level kinetics of photo-orientation induced by linearly polarized light and its subsequent thermal relaxation in the complexes of 2 and 4 with P4VP. 117 This study showed that, while the saturated orientation per azo of both 2 and 4 decreases with increasing azo content, 2 orients more than 4 and only 2 also drives photo-induced orientation of the passive H-bonded pyridine groups of P4VP. Furthermore, it was concluded that 4 undergoes mainly angular hole burning resulting from angular-dependent trans-cis isomerization, whereas for 2 there is a significant additional contribution from angular redistribution.…”
Section: à2mentioning
confidence: 74%
“…Supramolecular side-chain LCPs are usually formed by H-bonds between hydroxyl and cyano groups [ 90 , 99 , 100 , 101 , 102 ]. Wang et al employed 4-hydroxy-4′-cyanoazobenzene and poly(4vinylpyridine) with 4-phenylazophenol (P4VP) to construct H-bonded supramolecular azobenzene complexes (see Figure 3 ) [ 103 ]. Along with an increasing molar ratio of azobenzene groups to the pyridine ring of P4VP repeat units (F A ), H-bonding complexation, as well as the band intensity in infrared spectra, were enhanced.…”
Section: Hydrogen-bonded Supramolecular Self-assemblies Of Organicmentioning
confidence: 99%
“… Supramolecular complexes of poly(4vinylpyridine) (P4VP) with 4-phenylazophenol (A H , R = H) and 4-hydroxy-4′-cyanoazobenzene (A CN , R = CN), and photoinduced orientation as a function of time during orientation (laser on) of P4VP/A CN (100%) and P4VP/A H (100%). Reprinted with permission from reference [ 103 ]. Copyright (2018) American Chemical Society.…”
Section: Figurementioning
confidence: 99%